Hemoculturas: estudo da prevalência dos microrganismos isolados em uma unidade de terapia intensiva de um hospital oncológico do Maranhão - SOARES, Nídia Rubia Muniz Ramos (2020)
Bloodstream infection (ICS) is a major cause of morbidity and mortality in cancer patients. ICSs can be identified through blood culture, an exam that isolates and identifies pathogenic microorganisms in the blood, blood culture collections are routine in ICUs. This study aimed to assess the prevalence and susceptibility profile to antimicrobials of patients admitted to an Intensive Care Unit (ICU), of an oncology hospital located in the city of São Luís - MA. Tracing the susceptibility profile to the most used antimicrobials in the treatment of ICS, correlating the diagnosis with the clinical outcome. This is a retrospective, observational study, carried out with the aid of medical records data. In the period from 2016 to 2018, evolutions of the Hospital Infection Control Service (SCIH) of the unit and the microbiological reports of the laboratory were analyzed. Microorganisms were identified by Mass Spectrometry (MALDI-TOF). 240 of the 619 blood culture samples were positive. The results of the analyzes show that there is an association between the variables age and infection, and that the average age of infected patients is above 60 years. In the analysis of the prevalence of microorganisms isolated in the samples, we evidenced the predominance of Gram positive bacteria (46.7%), especially Staphylococcus epidermidis (10.4%) and Staphylococcus haemolyticus (9.6%). In the group of Gram negative bacteria, Klebisiella pneumoniae (11.7%) and Acinetobacter baumannii (10%) stood out. Most fungal infections were caused by Candida albicans (3.8%). Considering the susceptibility to antimicrobials, it was observed that the Gram positive bacteria Staphylococcus haemolyticus and Enterococcus faecalis, showed sensitivity to vancomycin, while the Gram negative bacteria showed a great diversity regarding resistance. K. pneumoniae (96.4%) to ampicillin, highlighting the resistance of (15%) to carbapenems and A. baumannii showed resistance to all drugs tested. Correlating infection, diagnosis and outcome (death), there was a prevalence in neoplasms of the Respiratory system (82%), CNS (78%) and hematological (77%). The results of the present study highlight the prevalence of multidrug-resistant microorganisms in (ICS), increasing mortality. Knowing the resistance profile serves to develop measures to reduce infection in patients admitted to the ICU.